Firesign The Electromagnetic History of Everything as Told on Nine Comedy Albums - Braddock, Jeremy (University of California Press, 2024)
A cultural clearinghouse of the American 1960s and '70s told through the story of the period's most important forgotten comedy group. This expansive book reclaims the Firesign Theatre (hazily remembered as a comedy act for stoners) as critically engaged artists working in the heart of the culture industry at a time of massive social and technological change. At the intersection of popular music, sound and media studies, cultural history, and avant-garde literature, Jeremy Braddock explores how this inventive group made the lowbrow comedy album a medium for registering the contradictions and collapse of the counterculture, and traces their legacies in hip-hop turntablism, computer hacking, and participatory fan culture. He deploys a vast range of material sources, drawing on numerous interviews and writing in tune with the group's obsessive and ludic reflections-on multitrack recording, radio, television, cinema, early artificial intelligence, and more-to focus on Firesign's work in Los Angeles from 1967 to 1975. This ebullient act of media archaeology reveals Firesign Theatre as authors of a comic utopian pessimism that will inspire twenty-first-century recording arts and urge us to engage the massive technological changes of our own era